2018
DOI: 10.3390/jlpea8030031
|View full text |Cite
|
Sign up to set email alerts
|

Clock Topologies for Molecular Quantum-Dot Cellular Automata

Abstract: Quantum-dot cellular automata (QCA) is a low-power, non-von-Neumann, general-purpose paradigm for classical computing using transistor-free logic. Here, classical bits are encoded on the charge configuration of individual computing primitives known as “cells.” A cell is a system of quantum dots with a few mobile charges. Device switching occurs through quantum mechanical inter-dot charge tunneling, and devices are interconnected via the electrostatic field. QCA devices are implemented using arrays of QCA cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The major role of clocking [23] is to control the flow of data and calculations. In [17], it is shown that the molecular QCA control results into enabling the feedback loops, versatile circuit grid and the support of feedback and memories.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The major role of clocking [23] is to control the flow of data and calculations. In [17], it is shown that the molecular QCA control results into enabling the feedback loops, versatile circuit grid and the support of feedback and memories.…”
Section: Related Workmentioning
confidence: 99%
“…The clocking fields can be used for clocking the molecular QCA. It can be implemented using an array of conductors [9] which is further used to determine the flow of data and calculations. Another advantage of using QCA clocks is to provide power gain for strengthening weak signals, enabling latching and permits adiabatic operations [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This will enable electric-field clocking of QCA cells using the z-component of an applied electric field. [24][25][26] A clocking field E z ẑ with sufficiently strong E z < 0 can over come the affinity of the mobile electron for the neutralizing charge on dot N , driving the cell from the "Null" state to the active state biased by neighbor interactions. As long as an adequate activating field is applied, the bit is latched.…”
Section: Introductionmentioning
confidence: 99%
“…Each QCA cell occupies only a few nm 2 in area, potentially offering high device densities of 10 14 cm −2 . Significant challenges must be solved for any realistic QCA implementation, such as limiting device power at high density using reversible gates 12,13 , designing robust wire crossings 14 and clocking networks 15,16 , and interfacing with the existing CMOS architecture.…”
Section: Introductionmentioning
confidence: 99%
“…In 2-state QCA, the two polarization states are defined by occupation of the antipodal sites and the clocking field is interpreted as a modulation of the inter-dot tunneling barriers 12 . In 3-state QCA, we introduce additional dots associated with a non-interacting or inactive null state 16 . By applying a relative voltage to the null dots we control the energy of the null state and can activate/deactivate cells in a clock zone.…”
Section: Introductionmentioning
confidence: 99%